An automated blender-cooker for paste making. - Mustapa Kamal, Siti Mazlina; Mohd Shariff, Intan Shaidatul Shima; Lee, Sze Ying (2010)

(untitled)
An automated blender-cooker (100) for paste making having an operating motor for providing rotational power to blades, a hopper unit for materials feeding, a cover lid closing open top opening of container, a safety holder for holding the container, a support base, a lifting support with lifting arm and controller body, characterized in that the automated blender-cooker includes: a) a blade shaft with a set of blade assembly, wherein the set of blade assembly includes upper blades and lower blades serve as blending and stirring means for the automated blender-cooker; b) a heating means, wherein the heating means is provided to heat up the container during the cooking operation; and c) a thermocouple, wherein the thermocouple is served as temperature sensor for the automated blender-cooker.